2006
DOI: 10.1007/s00253-005-0145-0
|View full text |Cite
|
Sign up to set email alerts
|

The effects of Lactobacillus-fermented milk on lipid metabolism in hamsters fed on high-cholesterol diet

Abstract: The objective of this study was to evaluate the effects of local Lactobacillus strains (NTU 101 and 102) on cholesterol-lowering effects in vivo. Thirty male hamsters were housed, divided into five groups, and fed on a cholesterol diet (5 g/kg diet) to induce hypercholesterolemia. Milk fermented by Lactobacillus paracasei subsp. paracasei NTU 101, Lactobacillus plantarum NTU 102, and Lactobacillus acidophilus BCRC 17010 was administrated for this study. After treatment with different fermented milk, blood was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
67
3
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(79 citation statements)
references
References 29 publications
8
67
3
1
Order By: Relevance
“…The strain used in this study had previously shown good survival in conditions simulating normal exposure to stomach acidity as well as high bile salt concentrations and additionally large bowel colonization can be inferred from the high counts of lactobacilli in the test group compared to the control group. The lactobacilli count increased steadily with time in the course of the study in agreement with several studies where administration of lactobacilli is positively correlated with significantly higher fecal lactobacilli counts [13,15,23]. In these studies the control is usually stable as in the present study.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The strain used in this study had previously shown good survival in conditions simulating normal exposure to stomach acidity as well as high bile salt concentrations and additionally large bowel colonization can be inferred from the high counts of lactobacilli in the test group compared to the control group. The lactobacilli count increased steadily with time in the course of the study in agreement with several studies where administration of lactobacilli is positively correlated with significantly higher fecal lactobacilli counts [13,15,23]. In these studies the control is usually stable as in the present study.…”
Section: Discussionsupporting
confidence: 80%
“…These could be due to effects on general health, alteration of microbial balance or other unknown factors. These results appear not to be supported by some other studies such as Chiu et al [15] where all groups of hamsters fed high cholesterol diet showed no significant differences in body weight gain, total food intake and food efficiency irrespective of administration of lactobacilli or not. Similarly Wang et al [13] found no significant differences in body weight gain; food intake and food efficiency in animals supplemented with a strain of L. plantarum and the control group fed high lipid diets.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…More recently, Jones et al (2004) showed the potential of artificial cell microencapsulated genetically engineered Lactobacillus plantarum for bile acids deconjugation to lower cholesterol. Animal studies have confirmed the in vivo cholesterol-lowering effects of selected probiotic strains (Chiu et al, 2005). Milk diets containing Bifidobacterium have been shown to improve serum lipids in rats as well as in humans with moderate hypercholesterolemia, suggesting a potential use of probiotics in lowering serum cholesterol (Roller, 2004).…”
Section: Iii2b : Functional Food: Conceptmentioning
confidence: 95%
“…Finally, it has been reported that microflora deconjugates and dehydroxylates bile acids Jones, 2004), metabolizes bilirubin (Saxerholt and Midtvedt, 1986), reduces cholesterol (Roller, 2004;Chiu, 2005), and degrades mucus glycoproteins produced by the intestinal epithelium's goblet cell lineage (Hooper et al, 2002).…”
Section: Ii2d : Signals From Peripheral Endocrine Factorsmentioning
confidence: 99%